2014
DOI: 10.12693/aphyspola.125.189
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocating Wear Behavior of Ductile Cast Iron Modified by Pulse Plasma Technology

Abstract: Wear resistance of ductile iron can be improved through di erent surface engineering techniques, each having some limitations and drawbacks. Recently, a new method called pulse plasma technology has been introduced, which through local reinforcement with inserts improves wear resistance of ductile iron without compromising other properties. This paper deals with the improvement of the wear resistance of ductile iron surface modi ed by pulse plasma technology using a tungsten electrode. The surfaces of the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Cheng et al [ 35 ] improved the wear characteristics of gray nodular cast iron by steady plasma beam surface melting. The detonation-based pulsed-plasma treatment proposed by Tyurin et al [ 36 , 37 ] was also used to modify ductile cast iron [ 38 ]. Cherenda et al [ 39 ] reported the application of a compression plasma flow to form a coating of the GCI surface.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [ 35 ] improved the wear characteristics of gray nodular cast iron by steady plasma beam surface melting. The detonation-based pulsed-plasma treatment proposed by Tyurin et al [ 36 , 37 ] was also used to modify ductile cast iron [ 38 ]. Cherenda et al [ 39 ] reported the application of a compression plasma flow to form a coating of the GCI surface.…”
Section: Introductionmentioning
confidence: 99%